Formação de professores: a educação a distância na formação continuada de professores do município de São Paulo - Maciel, Vanderli Jusiene dos Santos (2020)
The research object focuses on the continuing education of teachers from the municipal network of São Paulo, in the distance mode. The research object proposed by us sought to know, in a first phase and, after the data analysis, to analyse the teacher’s conceptions about the process of continuing education within the UniCEU network, in the city of São Paulo. The municipal network of São Paulo has about 60,000 education professionals, who work from early childhood education to high school. Thinking about the continuing education of these professionals, who work in the most diverse social contexts and who are geographically distant, is a great challenge. One of the strategies for investing in continuing education adopted by the municipality of São Paulo was the creation of the UniCEU Network (University in the Unified Centers), which has contributed to the continuing education of public-school teachers in your municipality. Our research problem stems not only from the reality of teacher training, but also from our concerns about the quality of non-classroom training. Therefore, from the problematization and construction of the research object, the nuclear question was derived: What are the teacher’s conceptions about the process of continuing education within the UniCEU network? We defined as a general objective, the following: Analyse the teacher’s conceptions about the contributions of the UniCEU network for the continuous training of teachers. For this, we investigated bibliographic references already produced on the concepts of continuing education and distance education by researchers in the field who address this theme and who contribute to the research question related to continuing teacher’s education and distance education. We follow a theoretical-epistemological model according to post-critical theories. From a methodological point of view, the research was of a qualitative and quantitative type, since we obtained empirical data from a questionnaire (quantitative) and discursive data from documents and interviews. From the study, it was possible to realize the importance of continuing education as a perspective for change and improvement in teaching practice and that the UniCEU network plays an important role in this process. The results point to the great relevance that the UniCEU network has in public policies for continuing education in the municipality and that distance education can be a positive alternative in this process.